COMPARATIVE RESEARCH ON RESISTANCE TEMPERATURE VARIATION OF COMPOSITION SAWDUST AND COCONUT COIR AS ISOLATOR RAW MATERIAL IN MAKING BOXES COOLING FISH (COOL BOX) - Hekar, M. Fazil; Syofyan, Irwandy; Hamid, Hamdi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The research was conducted in December 2014 in the laboratory material fishing gear (BAT) Department of Water Resources Utilization (PSP). The purpose of this study was to determine the best insulating material in between sawdust and coconut coir in defending the temperature remains low. The method used is experimental method. Carried out tests on six fish cooler box (coolbox) created, with the insulator sawdust and coconut coir mixed with tapioca flour and then the data analysis, descriptive. The result showed that of the three comparison sawdust and coconut fiber as a raw material is superior insulator coco with a ratio of 100% of raw materials to maintain the temperatures remain low for 10-11 hours.Keywords: Cooler Box Fish (coolbox). Insulator (insulation). Temperature.